Concentration and elemental composition of quasi-ultrafine particles in Upper Silesia - Rogula-Kozłowska, Wioletta; Mach, Tomasz; Rogula-Kopiec, Patrycja; Rybak, Justyna; Nocoń, Katarzyna (Oficyna Wydawnicza Politechniki Wrocławskiej, 2019)
The ambient concentrations and elemental composition of particles with aerodynamic diameters between 30 and 108 nm (quasi-ultrafine particles, q-UFP) were studied. The data came from 6 sites in Katowice and Zabrze, big cities in Upper Silesia, where particulate matter was sampled at urban background site and crossroads in Katowice and Zabrze, at highway in Katowice, and at urban road in Zabrze. The ambient concentrations of q-UFP and of 24 q-UFP-bound elements at these six sampling sites have been discussed in the paper. The q-UFP mass concentrations in Upper Silesia did not appear high, they were not higher than in other areas. The percentages of the total mass of the examined elements in the q-UFP mass suggest that in Upper Silesia, within a typical residential area, q-UFP consist mainly of primary matter. At the sites under strong influence of road traffic emissions, where the contributions of the examined elements to the q-UFP mass were small, most probably, carbonaceous matter and elemental carbon build the core q-UFP mass. The majority of the elements in q-UFP are anthropogenic. Clear effects of local PM sources can be seen on the ambient concentrations of q-UFP-bound Al, Si, S, Cl, K, Sc, Ti, V, Cd, Cr, Mn, Co, and Sb.
Environment Protection Engineering. Vol. 45, 2019, nr 1, s. 171-184
Keywords: ochrona środowiska; inżynieria środowiska